A multicenter REtrospective observational study of first-line treatment with PERtuzumab, trastuzumab and taxanes for advanced HER2 positive breast cancer patients. RePer Study. Issue 2 (1st February 2019) - Gamucci, Teresa; Pizzuti, Laura; Natoli, Clara; Mentuccia, Lucia; Sperduti, Isabella; Barba, Maddalena; Sergi, Domenico; Iezzi, Laura; Maugeri-Saccà, Marcello; Vaccaro, Angela; Magnolfi, Emanuela; Gelibter, Alain; et al.
ABSTRACT: We carried out a retrospective observational study of 264 HER2-positive advanced breast cancer (ABC) patients to explore the efficacy of first-line treatment with pertuzumab/trastuzumab/taxane in real-world setting. Survival data were analyzed by Kaplan Meier curves and log rank test. Median follow-up, length of pertuzumab/trastuzumab/taxane treatment and of pertuzumab, trastuzumab maintenance were 21, 4 and 15 months, respectively. The response rate was 77.3%, and the clinical benefit rate 93.6%. Median progression-free survival (mPFS) was 21 months, and median overall survival (mOS) was not reached. When comparing patients by trastuzumab-pretreatment, similar PFS were observed, although a longer OS was reached in trastuzumab-naïve patients (p = 0.02). Brain metastases at baseline and their development in course of therapy were associated with significantly shorter PFS (p = 0.0006) and shorter OS, although at a not fully statistically relevant extent (p = 0.06). The addition of maintenance endocrine therapy (ET) to pertuzumab/trastuzumab maintenance was associated with longer PFS (p = 0.0001), although no significant differences were detected in OS (p = 0.31). Results were confirmed by propensity score analysis (p = 0.003 and p = 0.46, respectively). In multivariate models, longer PFS was related to lower Performance Status (PS) (p = 0.07), metastatic stage at diagnosis (p = 0.006) and single metastatic site (p < 0.0001). An OS advantage was observed with lower PS (p < 0.0001), single metastatic site (p = 0.004), no prior exposure to trastuzumab (p = 0.004) and response to pertuzumab-based treatment (p = 0.003). Our results confirm that trastuzumab/pertuzumab/taxane is the standard of care as first-line treatment of patients with HER2-positive ABC even in the real-world setting. Moreover, the double-maintenance therapy (HER2 block and ET) is strongly recommended when feasible.